2019
DOI: 10.1139/bcb-2018-0301
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-3666 inhibits lung cancer cell proliferation, migration, and invasiveness by targeting BPTF

Abstract: A previous study by our group indicted that overexpression of bromodomain PHD-finger transcription factor (BPTF) occurs in lung adenocarcinoma, and is closely associated with advanced clinical stage, higher numbers of metastatic lymph nodes, the occurrence of distant metastasis, low histological grade, and poor prognosis. Down-regulation of BPTF inhibited lung adenocarcinoma cell proliferation and promoted lung adenocarcinoma cell apoptosis. The purpose of this study is to identify valuable microRNAs (miRNAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…Our study identified miR‐3666 as a novel miRNA target of circPVT1. Multiple studies have reported that miR‐3666 is a tumour suppressive miRNA in various cancers . Here, we demonstrate that miR‐3666 is also downregulated in HCC tissues and cell lines and its overexpression suppressed the proliferation of HCC cells, confirming a tumour suppressive function of miR‐3666 in HCC.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study identified miR‐3666 as a novel miRNA target of circPVT1. Multiple studies have reported that miR‐3666 is a tumour suppressive miRNA in various cancers . Here, we demonstrate that miR‐3666 is also downregulated in HCC tissues and cell lines and its overexpression suppressed the proliferation of HCC cells, confirming a tumour suppressive function of miR‐3666 in HCC.…”
Section: Discussionsupporting
confidence: 75%
“…Multiple studies have reported that miR-3666 is a tumour suppressive miRNA in various cancers. [35][36][37] Here, we demonstrate that miR-3666 is also downregulated in HCC tissues and cell lines and its overexpression suppressed the proliferation of HCC cells, confirming a tumour suppressive function of miR-3666 in HCC. Moreover, we found that miR-3666 expression was regulated by circPVT1 in HCC cells.…”
Section: Discussionsupporting
confidence: 69%
“…The optimal compound in this study, DC-BPi-11, is a potent inhibitor of BPTF-BRD (K D = 20.7 nM) and is selective over the other BRD family members screened. In the cell model of MV-4-11 leukemia cells, DC-BPi-11 reduced proliferation, blocked the cell cycle, and induced apoptosis, which is consistent with previous observations in BPTF genetic studies 34. DC-BPi-11 is expected to enable the further deeper investigation of the role of BPTF-BRD in transcriptional regulation through chemicalgenetic dissection.…”
supporting
confidence: 86%
“…Previously, miR-3666 was proposed as a tumor suppressor in several types of cancer. miR-3666 was shown to suppress cell growth in lung cancer by targeting BPTF (31). miR-3666 was also shown to suppress the expression of SIRT7 to impair the growth of NScLc cells (32).…”
Section: Discussionmentioning
confidence: 99%